2022
DOI: 10.3390/cancers14071791
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Hypoxia: Points of Interplay in Cancer

Abstract: Vitamin D is a hormone that, through its action, elicits a broad spectrum of physiological responses ranging from classic to nonclassical actions such as bone morphogenesis and immune function. In parallel, many studies describe the antiproliferative, proapoptotic, antiangiogenic effects of calcitriol (the active hormonal form) that contribute to its anticancer activity. Additionally, epidemiological data signify the inverse correlation between vitamin D levels and cancer risk. On the contrary, tumors possess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 226 publications
0
5
0
Order By: Relevance
“…A study showed that vitamin D3 can inhibit cell proliferation, invasion, and metastasis and promote apoptosis through the PI3K-Akt pathway ( Songyang et al, 2021 ). Vitamin D3 can also interfere with the metabolism of cancer cells, inhibit the growth and proliferation of cancer cells, and play an anti-cancer role through the HIF signaling pathway ( Gkotinakou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study showed that vitamin D3 can inhibit cell proliferation, invasion, and metastasis and promote apoptosis through the PI3K-Akt pathway ( Songyang et al, 2021 ). Vitamin D3 can also interfere with the metabolism of cancer cells, inhibit the growth and proliferation of cancer cells, and play an anti-cancer role through the HIF signaling pathway ( Gkotinakou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the combined effect of these factors, the proliferation, angiogenesis, immune escape, epithelial-mesenchymal transition and the ability of extracellular matrix remodeling of cancer cells are enhanced ( Mylonis et al, 2021 ; Semenza, 2021 ). The existing evidence suggests that ossifying triol can act on the signaling process of HIF pathway, blocking signal transduction, promoting apoptosis of cancer cells and exerting tumor suppressive effects ( Gkotinakou et al, 2022 ). Mitogen-activated protein kinase (MAPK) is an important member of the serine-threonine kinase family and is the main cell proliferation signaling pathway from the cell surface to the nucleus ( Dong et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is a characteristic feature of tumor microenvironment, which is known to contribute to cancer cell survival and proliferation. Hypoxia is of particular relevance in the development of solid tumors, which ensues due to the disorganized architecture of tumor vasculature, resulting in poor oxygen delivery particularly to inner core of cancer cells [26]. The development of hypoxia in tumors represents a poor prognostic value for cancer patients [27][28][29].…”
Section: Hypoxia Signaling and Hif-1 Stabilizationmentioning
confidence: 99%
“…This Special Issue of Cancers (two original articles, five reviews), presented by international experts in tumor hypoxia, focuses on the role of hypoxia, or low oxygen levels, in the development and progression of cancer. This Special Issue includes seven papers that discuss various aspects of hypoxia in cancer, including its effects on tumor growth, metastasis, and resistance to therapy [1][2][3][4][5][6][7]. Davis et al discussed the roles of the hypoxiainducible factor (HIF) signaling pathway and the alpha subunits HIF-1α and HIF-2α in driving tumor progression in the hypoxic tumor microenvironment.…”
mentioning
confidence: 99%
“…Gkotinakou et al discussed the interplay in cancer hypoxia focusing on vitamin D. They concluded that tumors have adaptive mechanisms that allow them to resist the anticancer effects of vitamin D, which are often attributed to the hypoxic microenvironment of solid tumors and the overexpression of hypoxia-inducible factors (HIFs). HIF-mediated signaling contributes to cancer cell survival, proliferation, and resistance to anticancer agents [4]. Janczy-Cempa et al focused on cellular adaptation to hypoxic stress, characterized by an increase in oxidoreductase activity, which can be exploited in the design of hypoxia-activated prodrugs (HAPs) and fluorescent turn off-on probes.…”
mentioning
confidence: 99%